SEC Based Method for Size Determination of Immune Complexes of Therapeutic Antibodies in Animal Matrix - Marta Boysen; Laura Schlicksupp; Ingeborg Dreher; Ralf Loebbert; Mario Richter (Journal of Immunology Research)
Therapeutic monoclonal antibodies (mAbs) represent a milestone in pharmacological development. Their superiority is based on the combination of high specificity, low toxicity, and long half-life that characterizes biologics. If biologics have Achilles’ heel, it is their potential immunogenicity. To better understand the impact of the size of immune complexes of mAbs on anti-drug antibody (ADA) dependent adverse reactions in Macaca fascicularis, we developed an efficient high-throughput size exclusion chromatography- (SEC-) based methodology that enables analysis of the size, size distribution, and ratio of free and ADA-complexed mAb in serum allowing for assessment of formation and clearance of circulating ADA-mAb immune complexes (CIC).